PENERAPAN ART THERAPY MEMBATIK COLET SEBAGAI UPAYA MEMELIHARA FUNGSI KOGNITIF LANSIA DI POSYANDU BAROKAH, KELURAHAN KLAMPIS NGASEM, KECAMATAN SUKOLILO, KOTA SURABAYA, PROVINSI JAWA TIMUR: The Application of Art Therapy Batik Colet as An Effort to Maintain Elderly Cognitive Functions in Posyandu Barokah, Kelurahan Klampis Ngasem, Kecamatan Sukolilo, Kota Surabaya, Provinsi Jawa Timur - Makhfudli; Kusnul Chotimah; Zenitha Rani; Elida Ulfiana (LPPM - STIKES Pemkab Jombang, 2020)
Klampis Ngasem is one of the areas in East Surabaya, precisely in Sukolilo sub-district, Surabaya. The target group in the community partnership program (PKM) is the Elderly Posyandu